DISTRIBUTION OF INCOME TAX BETWEEN PERIODS - Noles Monteblanco, Walter Adolfo (2014)
The main problems in accounting for the income taxes arises from the fact that the utility for financial pur-poses, can be very different from the utility a taxable use, with the effect that the tax shown in the income statement as tax charges income, bears no relation to the value shown in that state; and further, it may be the case, that there is a charge for income tax in the income statement when this is found to show an accounting loss.Whether the income tax is an expense that must be recognized to get to the net income or costs of doing business, focuses on the International Accounting Standard No. 12 (NIC 12). However, in our midst this invaluable principle has not yet dissemination should have. Limitation seeking to assist in overcomes this treaty, with the aim that, as a result of their unders-tanding and application rather Financial Statements reasonably reflect the financial position and results of operations in accordance with the International Financial Reporting Standards.